Rizbrunana: advances in high-fibre biscuit using brown rice and banana peel / Nurul Hafizah Mohd Yasin ... [et al.] - Mohd Yasin, Nurul Hafizah; Bah Simpong, Derweanna; Abd Hadi Khan, Nur Farihin; Ibrahim, Mazne (2021)
The consumption of brown rice is limited among Malaysians. This study was conducted to develop a product of high-fiber brown rice biscuits made from Saba’ banana peel flour. Out of the eight formulations developed, hedonic scale sensory test results showed samples of F6 formulation with a combination of brown rice flour (31.5%) and 13.5% banana peel flour. F6 had the highest mean value for each attribute examined and significant differences (p <0.05) were observed in regard to the colour, aroma and appearance of the biscuits. The results of the proximate test analysis shows high fiber brown rice and banana peel flour biscuits contains 92 ± 0.07% moisture, 2.10 ± 0.27% ash, 9.23 ± 0.34% protein, 18.98 ± 1.62% fat, 6:42 ± 0.05% crude fiber, 7:53 ± 0.00% dietary fiber content and 60.16 ± 1.67% carbohydrate and the amount of energy supplied was 463.44 kcal per 100g. Brown rice with banana peel flour biscuits are expected to have a storage life span of more than 8 weeks. Finally, the consumer tests showed that this biscuits product has good potential to be commercialized from the positive response of 77% of respondents said they would buy these biscuits if they are available in the market.